2021
DOI: 10.18502/ijrm.v19i9.9710
|View full text |Cite
|
Sign up to set email alerts
|

Success rate and ART outcome of microsurgical sperm extraction in non obstructive azoospermia: A retrospective study

Abstract: Background: The management of non-obstructive azoospermia (NOA) disease relies on microdissection testicular sperm extraction (micro-TESE). Few studies have assessed the role of micro-TESE in men with NOA in our country. Objective: The aim of the current study was to investigate the success rate of micro- TESE. Materials and Methods: This retrospective descriptive-analytical study was conducted on 463 men with NOA in Yazd Reproductive Sciences Institute during September 2017 through September 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…Therefore it could be believed that the NOA patients in the three groups could be compared. This result is consistent with Vahidi's study, except for the different fertilization rate (Vahidi et al, 2021). This suggested that the quality of embryos formed with sperm obtained by micro-TESE surgery from NOA patients of different causes is similar.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore it could be believed that the NOA patients in the three groups could be compared. This result is consistent with Vahidi's study, except for the different fertilization rate (Vahidi et al, 2021). This suggested that the quality of embryos formed with sperm obtained by micro-TESE surgery from NOA patients of different causes is similar.…”
Section: Discussionsupporting
confidence: 92%
“…This has been supported by a recent study as well (Pavan‐Jukic et al., 2020). On the other hand, many studies and meta‐analyses have shown that FSH and LH levels are a predictor of TESE success and as FSH and LH levels increase, the sperm retrieval rates decrease (Boitrelle et al., 2011; Liu et al., 2020; Majzoub et al., 2021; Vahidi et al., 2021; Yang et al., 2015). Also the data about serum testosterone levels in predicting TESE success are indecisive in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…12 Vahidi et al conducted research with 130 men who underwent Micro-TESE -ICSI cycle with results of successful fertilization, biochemical pregnancy, and live birth were seen in 111 (85,4%), 29 (22,3%), 29 (22,3%), and 14 men (10,75%), respectively. 13…”
Section: Discussionmentioning
confidence: 99%